KEDUDUKAN ANAK PEREMPUAN SEBAGAI ANAK TUNGGAL DALAM SISTEM PEWARISAN PADA MASYARAKAT ADAT BALI ( The Position Of Daughter As The Only Children In The Inheritance System In Balinese Society ) - Wayan Jordi; Kahar Lahae; Sri Susyanti (Universitas Labuhanbatu, 2022)
Inheritance customary law is the rule of customary law that regulates how the inheritance or inheritance is passed on or divided from the heir to the heirs from generation to generation. Indigenous Balinese people with a patrilineal family system, causing only descendants with the status of kapurusa (male) are considered to be able to take care of and carry on family responsibilities. The problem in this research is